2021
DOI: 10.2147/rrtm.s311476
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and Associated Factors Among Adult Tuberculosis Patients in Jigjiga Public Health Facilities, Somali Region, East, Ethiopia

Abstract: Background Tuberculosis and undernutrition are the public health concerns of people living in middle and low-income countries. When patient develops TB, undernutrition is not only a risk factor for progression of latent TB infection to active disease, but also intensifies the risk of drug toxicity, relapse and death. Nutritional supplementation in patients with TB is associated with faster sputum conversion, higher cure and treatment completion rates, and body-weight gain. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Thus, male counterparts were 42% less likely to experience food security. This finding is supported by studies conducted in different settings, such as South Africa (38), the Somali Region (31), Adama (40), and lowincome countries (41). The possible justification could be attributed to the fact that men have greater access to social capital and pathways out of crisis; for instance, their income pays off previous debts and secures new farm loans, whereas women frequently face severe time constraints due to their household food-security roles.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, male counterparts were 42% less likely to experience food security. This finding is supported by studies conducted in different settings, such as South Africa (38), the Somali Region (31), Adama (40), and lowincome countries (41). The possible justification could be attributed to the fact that men have greater access to social capital and pathways out of crisis; for instance, their income pays off previous debts and secures new farm loans, whereas women frequently face severe time constraints due to their household food-security roles.…”
Section: Discussionmentioning
confidence: 76%
“…Despite the commitment of various stakeholders and the government, the prevalence and determinants of food security, as well as tuberculosis, which are thought to be the direct and underlying causes of undernutrition, continue to be a problem. Moreover, there are a few studies conducted in Ethiopia that pointed out that food insecurity among Tb patients is a major widespread problem (11,21,31). Furthermore, there is a paucity of documented evidence regarding the problems under study generally at the county level and particularly at the study area level, so the purpose of this study was to assess factors associated with food insecurity among adult tuberculosis patients attending public health facilities in Grawa district, Eastern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that 60.4% of patients with pulmonary TB had undernutrition, in which one-fifth of the sample (20.4%) were severely malnourished. The prevalence of underweight among TB patients varies across studies and continents, mostly reported over 40% [14][15][16] . A meta-analysis involving 48,598 participants reports a prevalence of malnutrition of 48.0% (95% CI, 40.9-55.2%), in which the prevalences of mild, moderate, and severe malnutrition are 21.4%, 14.0%, and 29.4%, respectively 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This secondary immunodeficiency increases the host's susceptibility to infection and thus increases the risk for developing TB. TB in turn causes reduction in appetite, macro-and micronutrient malabsorption, and altered metabolism, leading to wasting and a poor nutritional status 12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although several small-scale studies in Ethiopia have described the relationship between undernutrition and TB at the individual level [31][32][33], the spatial codistributions and ecological level drivers of undernutrition and TB at a lower administrative level are yet to be investigated. This study, therefore, set out to investigate the spatial codistribution and socio-climatic factors of undernutrition and TB in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%